The Relationship Between Tool and Technique in Heidegger’s Philosophy of Technology - Čapanauskas, Tadas (Problemos, 2019)
[full article and abstract in Lithuanian; abstract in English]The aim of the article is to reveal the difference between the tool (Zeug) and the technique (Technik) in Heidegger’s philosophy of technology. Differences point to the problem of the world constitution. While Heidegger presents Dasein’s relation with the tool as “ready-to-hand” (Zuhandenheit), he presents the relation with the technique as diametrically opposite. Technology which is emerging from natural sciences tied up with machination (Machenschaft) by the philosopher is presented as Dasein’s creative powers in the context of suppresing medium establishment (Gestell). The article reveals a twofold problem. First, it shows the ontological differences between a tool and technique. Second, it shows the ambiguity of the ontology of establishment. Establishment for Heidegger is not merely the ultimate mechanism of technical mastering but also a “saving power”.
Keywords: Martin Heidegger; technology; tool; establishment; Gestell; machination